Diversifikasi pangan beras analog berbahan dasar gatot (singkong fermentasi) dan jagung : formulasi dan kualitas fisikokimia - Ratnaduhita, Astari; Kholis, Muhammad Nur; Dwicahyo, Agung (Program Studi Ilmu dan Teknologi Pangan, Universitas Yudharta, Pasuruan, 2025)
The number of rice imports in Indonesia is increasing every year, so efforts to diversify food are needed to achieve the Nusantara's food security by making alternative rice or analog rice. The basic ingredients chosen utilize corn commodities from Ponorogo and gathot (fermented cassava) production from DIY which is less than optimal in processing and utilization so far. This study aims to design an analog rice formulation with gathot and corn as the basic ingredients and evaluate the physicochemical quality of the analog rice. This research used gathot (fermented cassava) from Gunungkidul sub-district, Yogyakarta and corn from Siman sub-district, Ponorogo which were processed into analog rice using the experimental method. This research was designed using a Completely Randomized Design (CRD) with the treatment of variations in the concentration of gathot flour (TG) and corn flour (TJ), namely: TJ 100% (T0); TJ 75%: TG 25% (T1); TJ 50% : TG 50% (T2); TG 100% (T3). Research data were analyzed using ANOVA with a significance level of 5% for testing variables including water content, water absorption and cooking time. The results showed that variations in the combination of corn flour and gathot flour in this analog rice had a significant effect (<0.00) on the value of moisture content (0.39-3.86%); water absorption (1.08-2.51%) and cooking time (14 minutes 14 seconds to 29 minutes 30 seconds). The treatment with a combination of 75% corn flour and 25% gathot flour became the best treatment of analog rice in this study because it showed similar quality to the standard analog rice.Â